THE PROBLEM OF INDONESIAN CONTRACT BRIDES IN CHINA AND ITS IMPLICATIONS FOR CROSS-BORDER MARRIAGE - Mei, Liu Xiang (International Review of Humanities Studies, 2024)
The rise of Indonesian contract brides in China has become a major focus that requires urgent action to protect their rights and well-being. The initiative aims to prevent exploitation in the context of cross-border marriages and ensure that such marriages are conducted fairly and legally. This situation arises from a number of factors, including difficult economic conditions, unlicensed intermediary operations, and a strong desire to live more prosperously. It also deals with issues of commercial marriage, human trafficking, and marital fraud, which require a careful and coordinated approach. Therefore, China should take steps to renew the international marriage law, enhance cooperation with Indonesia, and effectively address these issues to promote the healthy and stable development of cross-border marriage.